Internal Management of Family System According to the Forgiveness Verses and Traditions (based on short-term release-disclosure intervention) - Masoud Azarbayejani; abbas pasandide; Masoud Janbozorgi (اخلاق وحیانی, 2017)
Considering the importance of family and its problems, on the one hand, and the capability of Islamic texts to solve family problems, on the other hand, this paper aims to investigate this question: what is the correct response to the mistakes or bad functions of one of the spouses in a family system. In other words, the purpose is to search for the best therapeutic responses in religious texts for rebalancing the family, when there is a wrong or inappropriate behavior. Our method is a qualitative content analysis. A Hadith from Imam Ali (pbuh) says: “if I do good things, she will thank, and if I do evil things, she will forgive,” which presents the dual situation of good-doing and evil-doing. This hadith has been narrated in numerous sources, including Al-Ja'fariyat (or al-'Ashathiyat), Ravandi's Al-Navader, Majlesi's Biḥār al-Anwār, Mirza Husain Tabarsi's Mustadrak Al-wasa'il. The main theme of this hadith can also be found in many verses of the Holy Quran. In addition, the pillars of intervention based on amnesty and forgiveness in the areas of maladjustment of harassment to the wife, search for the correct response to the spousal bad functions (superior coping), the effects and consequences of passing and forgiveness, and finally the training of forgiving skills based on various verses and hadiths has been tracked. The conclusion of this essay is that the basic principle in responding to the wife's mistakes is to forgive her. It is noteworthy that forgiveness reaction is the counterpart and complement of gratitude.